The Miharamycins and Amipurimycin: their Structural Revision and the Total Synthesis of the Latter. (1st July 2019) - Wang, Shengyang; Zhang, Qingju; Zhao, Yachen; Sun, Jiansong; Kang, Wenjia; Wang, Fei; Pan, Haixue; Tang, Gongli; Yu, Biao
Abstract: The structural puzzle of amipurimycin, a peptidyl nucleoside antibiotic, is solved by total synthesis and X‐ray diffraction analysis, with the originally proposed configurations at C3′ and C8′ inverted and those at C6′, C2′′, and C3′′ corrected. A similar structural revision of the relevant miharamycins is proposed via chemical transformations and then validated by X‐ray diffraction analysis. The miharamycins bear an unusual trans ‐fused dioxabicyclo[4.3.0]nonane sugar scaffold, which was previously assigned as being in the cis configuration. Abstract : Das letzte Puzzlestück : Die Strukturen von Amipurimycin und den Miharamycinen wurden durch chemische Synthese und Röntgenbeugung aufgeklärt. Die Konfiguration von Amipurimycin wurde revidiert. Die Miharamycine haben ein trans ‐anelliertes Dioxabicyclo[4.3.0]nonan‐Zuckergerüst, dem zuvor eine cis ‐Konformation zugewiesen worden war.